The detection and comparison of antimicrobial resistance pattern of vancomycin-resistant enterococci and Salmonella isolated from eggs of commercial layers and free-range chickens - Hassan, Latiffah; Suhaimi, S. Zaleha; Abdul Aziz, Saleha (Veterinary Association Malaysia, 2005)
The prevalence of vancomycin-resistant enterococci (VRE) and Salmonella in eggs produced by free-range chickens and commercial layers was compared to establish the microbial safety of the food and to determine if management, especially feeding management and the environment, playa role in the occurrence of the two organisms. The isolates were subjected to an antibiotic sensitivity test to determine the antibiotic resistance pattern. It was observed that there was a slight difference in the occurrence of the organisms and in the pattern of antibiotic resistance of isolates from free-range chickens' eggs and those from commercial layers. Enterococcus was detected in 10% and 7.7% of eggs from commercial layers and free-range chickens respectively. Salmonella spp occurred in 7.5% and 12.8% of commercial layers and free-range chicken eggs, respectively. The study suggests that free-range eggs may not be as wholesome as often believed and that the environment plays an important role in the development of antibiotic resistance.